SYNTHESIS, MOLECULAR DOCKING AND ANTIBACTERIAL EVALUATION OF SOME NOVEL N-4 PIPERIDINYL DERIVATIVES OF SPARFLOXACIN - Kumar, Hemanth K Sudheer; H, Parameshwar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study envisage a series of sparfloxacin derivatives were synthesized (Q1-Q10) with added derivatives such as aminomethyl benzenesulfenyl, methyl (methylamino)benzenesulfenyl, amino methyl benzoyl chloride, nitromethyl benzoyl chloride, dimethyl phenylamino, methoxymethyl phenylamino, dimethyl oxopyrazol, methyl dioxopyrrolidine, methyl oxopyrrolidine, and N-Boc amino methyl methylpyrrolidine through N-Piperzinyl linkage. Methods: All the newly synthesized compounds were characterized by infrared,1H nuclear magnetic resonance, mass spectrometry, and elemental analysis technique, screened for docking stimulation to find out binding modes of synthesized derivatives with 3FV5 and 3IMW, and evaluated for in vitro antimicrobial activity. Results: From this study, it was found that the compound Q5 showed good antibacterial activity against Gram-positive (Staphylococcus aureus) and compound Q4 showed good antibacterial activity against Gram-negative (Escherichia coli) in comparison with standard drugs (ciprofloxacin and sparfloxacin). The zone of inhibition and minimum inhibitory concentrations studies performed to synthesized compounds. The correlation between experimental data (minimum inhibitory concentrations) and docking score suggests that penetration for docking simulation is good to mild in reproducing experimental orientation of these synthesized compounds. Conclusion: The analogs of sparfloxacin are suggested to be potent inhibitors with sufficient scope for further exploration.